Effect of lactic acid as plasticizing agent on the tensile and biodegradable properties of corn cob powder/polyvinyl alcohol blend film - Chai, Wan Qi (2023)

(untitled)
In this study, the blended film was prepared from a PVA/CCP/lactic acid blended film using the solution casting method. Blended was prepared by modifying the composition of lactic acid using the one-factor-at-a-time (OFAT) method. Attenuated total reflectance (ATR) spectroscopy was used to identify the functional group of CCP and each PVA/CCP/lactic acid blended film. Beside, thermogravimetric Analysis (TGA) was used to determine the thermal stability of CCP and each PVA/CCP/lactic acid blended films. In the others hand, the mechanical properties of each PVA/CCP/lactic acid blended film were examined using a tensile test to check their tensile strength, elongation at break and elastic modulus. According to the results, the elastic modulus and tensile strength with the highest values were 14.09 MPa and 445.7 MPa, respectively, and the elongation at break value was 15.12%. After the tensile test, the cross-sectional morphology of the PVA/CCP/lactic acid blended films with the lowest, medium and maximum tensile strengths was examined using scanning electron microscopy (SEM). In addition, a soil burial test called biodegradability test was conducted to study the biodegradability. According to the results, among all the blended films, the films containing 1.5 ml of lactic acid had the highest biodegradability.